Obstacles to Implementation of Professional Pediatric Nursing - M Aghdami; F Alhani (Iran University of Medical Sciences, 2010)
Background and Aim: The basic role of nurses is the restoration of health through caregiving activities. The nurses can do all of their responsibilities if they are informed of duty description. One of the most important duties of nursing service head is to prepare staff nurses and to ensure their performance to achieve assigned activities. The aim of this study was to determine obstacles to implementation of professional pediatric nursing job descriptionin the pediatric hospitals located in Tehran, Iran.   Materials and method: This research was a descriptive study in which 63 staff nurse and nurse manager, working in pediatric hospitals, were recruited by proportional stratified random sampling. The research instruments were a demographic data sheet and self-report questionnaire about obstacles to implementation of professional duties.   Results: The mean age of the subjects was 33.92±8.92 years, the mean years of experience was 9.19±8.46, and the mean years of work experience in pediatric unit was 7.97± 7.42. All the subjects were female, out of which 74.6% were staff nurses and the remaining were nursing managers. The results showed that the most important obstacles were, "the improper ratio of nurses to patients" (management dimension), "shortage of continuing and in-service education courses" (educational dimension), "the lack of space for doing professional duties" (environmental dimension), and finally, "inadequate recreational facilities for nursing personnel" (motivational dimension).   Conclusion: For overcoming the abovementioned obstacles, some strategies were developed and scored and finally, the most salient strategy, "establishing a national committee for review, reassessment and implementation of professional pediatric nursing job description" was considered to be executed.